Ukrainian companies on the Warsaw Stock Exchange: Current state and future trends - Paweł Perz; Piotr Każmierkiewicz; Ulyana Dzyuma; Rusłan Harasym; Paweł Bochenek; Mihail Cebotari (e-Finanse: Financial Internet Quarterly, 2011)
As a result of globalization trends many businesses are able to raise capital not only in their domestic market, but also abroad. Among the stock exchanges which have managed to attract foreign companies is the Warsaw Stock Exchange. Over the past few years many companies from Ukraine have chosen to be listed on the Warsaw Exchange. This article provides an analysis of the conditions linked to raising capital for Ukrainian companies on the Polish market.
Keywords: G14; F23; E44; 330; Warsaw Stock Exchange; investment; Ukrainian companies